1987
DOI: 10.1021/bi00382a041
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-promoting phorbol ester amplifies the inductions of tyrosine aminotransferase and ornithine decarboxylase by glucocorticoid

Abstract: In adrenalectomized rats, the tumor-promoting phorbol ester 12-O-tetradecanoylphorbol 13-acetate (TPA) markedly enhanced the inductions of tyrosine aminotransferase (TAT) and ornithine decarboxylase by glucocorticoids, even with sufficient concentration of glucocorticoids to have a maximal effect, whereas it had no effect on TAT activity and increased ornithine decarboxylase activity only slightly in the absence of glucocorticoids. Phorbol derivatives and components of TPA such as 4 beta-phorbol, phorbol 12-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Activation of PKC by treatment with TPA enhances the glucocorticoid-induced expression of liver tyrosine aminotransferase (TAT) (31,32). It was suggested that PKC may enhance glucocorticoid-induced TAT expression by facilitating the translocation of the glucocorticoid receptor (GR) to the nucleus (31).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PKC by treatment with TPA enhances the glucocorticoid-induced expression of liver tyrosine aminotransferase (TAT) (31,32). It was suggested that PKC may enhance glucocorticoid-induced TAT expression by facilitating the translocation of the glucocorticoid receptor (GR) to the nucleus (31).…”
Section: Discussionmentioning
confidence: 99%
“…With glucocorticoids, phorbol esters enhanced hormone induction of hepatic enzymes (64), and inhibitors reduced this induction as well as nuclear translocation of the receptors (65). Protein kinase C activators, however, inhibited glucocorticoid-dependent transcription in NIH-3T3 cells (66).…”
Section: Effects Of Kinase Activators and Inhibitorsmentioning
confidence: 97%
“…TPA regulates gene transcription by phosphorylation of transcription factors AP-1 in a number of cases (Angel et al, 1987). The glucocorticoid dependence of the TPA induction of D-I1 might be due to an effect on the transcription of the D-I1 gene, as for hepatic tyrosine aminotransferase (Kido et al, 1987). The effect of TPA was transient, probably due to the loss of protein kinase C (Fishman et al, 1987).…”
Section: Discussionmentioning
confidence: 99%